DAMPAK KILAT TERHADAP PENGLIHATAN MANUSIA PERSPEKTIF AL-QUR’AN DAN SAINS - Zulfikri Zulfikri; Siti Khamidatus Sholikhah (Tanzil: Jurnal Studi Al-Quran, 2023)
Lightning is a natural phenomenon that is both beautiful enough to be seen with the eyes and a threatening natural occurrence at the same time. Various sources define lightning as a very fast light containing an electric current that is then delivered to a cloud or the ground. The transmission of electric current when lightning occurs causes a threat to humans, which is one of these lightning threats as studied in the title of this study. The research method used is qualitative research with the study of the library using a case approach. The analysis used in this study is descriptive analysis. The problem raised is how the impact of lightning on the human eye is seen from the perspective of the Qur’an and science. The result or conclusion was found to be that lightning, from the perspective of the Qur'an, has a variety of meanings, with its very bright ability to blind or eliminate sight when seen by the eye. From a scientific standpoint, lightning can cause red eyes and blurred vision. Which, if not handled properly, can result in permanent blindness.